Industry 4.0, Cleaner Production, and Circular Economy: An important agenda for improved Ethical Business Development. (1st December 2021) - Luthra, Sunil; Mangla, Sachin K.; Lopes de Sousa Jabbour, Ana Beatriz; Huisingh, Donald
Abstract: This editorial was designed to summarize the contents and key theoretical aspects highlighted in this Special Volume (SV) on "Industry 4.0, Cleaner Production and Circular Economy: An Agenda for Ethical Business Development". The authors briefly reviewed the concepts of Industry 4.0 (I4.0), Cleaner Production (CP) and Circular Economy (CE) that provide the basic foundation for this SV. A summary of the key theoretical themes, which guided and motivated the authors to submit their articles the SV was presented next. The editorial highlights the main outcomes of the selected papers in the SV. Twenty-one papers were selected that are grouped in five categories. The categories are- I4.0 application based, approaches, decision-support based tools, policy-based research, empirical investigations, and procedural synergies from integrated implementation of I4.0 and CE concepts and approaches. In the context of these categories, the 'decision-based category' was the most frequently represented in the submitted papers. Because the systematic integration of I4.0 tools and approaches with CE, and CP is still in a nascent stage, the contributions of this SV will certainly be helpful for industry, academicians and society. One very interesting aspect of this SV were the contributions, based on the actual benefits of integrated implementation of I4.0 for CE and CP. There is a huge gap and lack of such applications based research in the literature which this SV highlights in several ways. Finally, the main theoretical dimensions and the practical approaches adopted by the SV's authors are reviewed. This editorial was concluded with a summary of the corporate managerial implications presented in the papers of this SV.